Antioxidative effects of leaves from Azadirachta species of different provenience - Pongtip Sithisarn (2018)
Twenty extracts of leaves from Azadirachta plants (Siamese neem tree of different provenience, neem tree and marrango tree), a traditional medicine, and frequently eaten in large amounts as parts of meals in Thailand, showed proportionality between total phenolics and radical-scavenging as measured, as reduction of Fremy's salt by ESR-spectroscopy. Scavenging effect of extracts from the neem tree was significantly lower than those of the Siamese neem tree and the marrango tree. The ability of the extracts to trap carbon-centred 1-hydroxyethyl radicals indicates prooxidative activity for a very high concentration of extract. The extracts were found to be efficient scavengers of compounds known to initiate lipid oxidation, as demonstrated by rate constants (25 °C) for reaction with ferrylmyoglobin: k = (1.7 ± 0.3) × 103M-1s-1at pH 5.5 and k = (7.7 ± 1.4) × 102M-1s-1at pH 7.4, respectively, and with riboflavin triplet-state: k = (1.30 ± 0.02) × 109M-1s-1at pH 7.4. The rate constants for deactivation of ferrylmyoglobin by the extracts were larger than the rate constant for deactivation by the pure phenolic compounds present in the extract, demonstrating synergistic effects. All extracts showed high efficiencies as chain-breaking antioxidants. This was indicated by lowering of oxygen consumption rates in a peroxidising lipid emulsion, suggesting a role as dietary antioxidants. Siamese neem tree leaf extracts were found to interact with α-tocopherol in peroxidising liposomes, resulting in synergistic effects. © 2007 Elsevier Ltd. All rights reserved.